The (Father Almighty) God we worship: the epistemological role of liturgy in christian theology - Grassi, Martín (2024)
Fil: Grassi, Martín. Pontificia Universidad Católica Argentina. Facultad de Filosofía y Letras. Departamento de Filosofía; Argentina